Relevansi Pembiayaan KPR Indent iB dengan Ketentuan DSN-MUI dan PSAK 104 - Arista Fauzi Kartika Sari (Journal of Islamic Economic Studies, 2025)
This study aims to examine the implementation of the KPR Indent iB product at BTNSyariah and its compliance with Fatwa No. 06/DSN-MUI/IV/2000 concerning Istishna Sale and Purchase and PSAK 104 Istishna Accounting. The urgency of this study is to examine the principles and compliance of accounting recognition for istishna contracts in the KPR Indent Ib product at BTNSyariah. This study uses a qualitative method, with primary data collection through interviews and secondary data through the required documents. The result is that the KPR Indent iB product from BTN Syariah is in accordance with the provisions of Fatwa No. 06/DSN-MUI/IV/2000 concerning Istishna Sale and Purchase, namely an explanation of the payment and time period that must be submitted at the beginning, and carried out in accordance with the agreement of both parties. In accounting, the payment process has been automated using the banking system in accordance with the provisions of PSAK 104.